المنهج الاجتماعي في النقد الأدبي العربي الحديث الرواية الجزائرية أنموذجا - أبو هيف, عبد الله (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
تناول البحث بعد التمهيد التأطير النظري للنقد الاجتماعي من غلبة الاتجاه الإيديولوجي لفترة طويلة من الزمن لارتباط الاتجاه الاجتماعي بالنقد الماركسي باسم اجتماعية الأدب وأولوية نقد موضوعاته ومضامينه وقضاياه العامة، إلى الاتجاه البنيوي التكويني، لارتباط الاتجاه الاجتماعي بالبنيوية وتأويلاتها ورؤى العالم فيها داخل البنية النصية وتعالقاته مع الخصائص الثقافية. عرّف البحث في القسم الثاني أبرز الجهود في تطبيق النقد الاجتماعي الروائي المطبوع في مؤلفات نقدية، وتوزع التعريف إلى أبرز الكتب النقدية وجماليات الرواية التي مارست النقد حول الرواية المغاربية بعامة والرواية الجزائرية، مثل كتاب «الرواية العربية الجزائرية ورؤية الواقع» (1993) لعبد الفتاح عثمان (مصر)، و«الرواية المغاربية – الجدلية التاريخية والواقع المعيش، دراسة في بنية المضمون» (2002) لإبراهيم عباس (الجزائر)، و«تجربة الطاهر وطار الروائية بين الإيديولوجيا وجماليات الرواية (2004) للكاتبة لينة عوض (الأردن). ختم البحث باستنتاجات عن مضامين النقد الاجتماعي الروائي. In the first part, this research deals with the theoretical framework of social criticism starting with the domination of the ideological aspect which has prevailed for a long period of time. This is the result of the connection of the social approach to Marxist criticism under the name of the socialism of literature, and the priority of criticizing its subjects, contents, and general external issues. Then, we turn to the structural framework to highlight the connection of the social trend to structuralism and its interpretations and visions of the world reflected through its textual, structural, and interaction with cultural criticism. In the second part, this study introduces the best efforts, printed in critical texts, of applying social criticism to fiction. This introduction is divided into two parts: the first is about the best critical texts which used criticism in the novel of Arab West-African countries, in general, and the Algerian novel, in particular. For example, The Arab Algerian Novel and Vision of Reality (1993) by Abd al-Fattah Othman (Egypt), and The Novel in Arab West-African countries: History and Reality: A study in the structural content (2002) by Ibrahim Abbas (Algeria), in addition to Al-Taher Wattar’s Experience: between Ideology and the Aesthetics of the Novel (2004) by Lina Awad (Jordan).This research concludes with general remarks about the application of social criticism to fiction.